Analisis Brand Ambassador Grup K-Pop EXO Sebagai Strategi Ekspansi Pemasaran Produk Scarlett Whitening - Mutiara Shalsabilla; Hadita Hadita (Universitas 45 Surabaya, 2023)
One of the impacts of the globalization era is related to the influx of cultural elements from other countries. The phenomenon of globalization is also able to connect countries through trade cooperation, cultural exchange, investment, technological advances and others. Some foreign cultures have begun to dominate Indonesia, whether from trends, music, movies, or the habits of life of other countries, but Indonesians are quite good at handling this phenomenon. Meanwhile, through its marketing expansion strategy, Scarlett Whitening utilizes the phenomenon that Indonesia has been named as the country with the highest number of K-pop fans or what we usually hear as K-popers in the world because of people's enthusiasm for South Korean culture, such as movies, music, drama or beauty trends in South Korea.